Association of Chemotactic Chemokine Ligand 5 Polymorphisms with the Risk of Developing Severe Enterovirus 71 Infection - Li, Mao-zhong (Am J Trop Med Hyg, 2015)
Respiratory damage is a main manifestation of severe Enterovirus 71 (EV71) infection. Polymorphisms of -403G/A (rs2107538), -28C/G (rs2280788), and In1.1T/C (rs2280789) in chemotactic chemokine ligand 5 (CCL5) have linked with many respiratory diseases. In this study, we explored the possible correlation of CCL5 polymorphisms with severe EV71 infection. Blood samples were obtained from 87 children hospitalized for EV71 infection. Fifty-seven healthy children were enrolled as asymptomatic controls. Genotype and allele frequencies were analyzed by logistic regression analysis. There were statistically significant differences in polymorphisms of CCL5 -403G/A and In1.1T/C for dominant model (P = 0.016; P = 0.027) and additive model (P = 0.010; P = 0.019) between patients with severe EV71 infection and asymptomatic controls. With ordinal logistic regression model analysis, statistically significant differences were found between polymorphisms of CCL5 (-403G/A) (P = 0.034) with the severity of EV71 infection after adjusting for age. The frequency of A-C-C haplotype was significantly higher in EV71 infection patients than controls (P = 0.032). These results suggest that CCL5 -403G/A and In1.1T/C polymorphisms may contribute to severe EV71 infection and individuals with haplotype of A-C-C may exhibit higher risk of developing severe EV71 infection. These findings may provide insights into pathogenic and protective mechanisms of severe EV71 infection.